Advances in Antioxidative Bioactive Macromolecules. Issue 1 (June 2020) - Song, Ruirui; Wu, Qi; Yun, Zhenyu; Zhao, Lin
Abstract: Oxidative stress has been implicated in the pathogenesis of various chronic diseases such as cardiovascular disease, cancer, coronary heart disease, and arthritis. The antioxidative bioactive macromolecules, as evidenced by substantial studies, can effectively scavenge reactive oxygen species (ROS) and free radicals or mediate the immune system of the body to regulate the redox level, arousing the concern of numerous researchers on their antioxidative activities. An overview was carried out in this paper emphasizing on the types, antioxidant activities, application fields, and preparation methods of antioxidative biomacromolecules, which is expected to provide theoretical basis for the development and utilization of antioxidative biomacromolecules, as well as their applications in the fields of biomedicine, functional foods and skin care products.